Immunohistochemical localisation of urogastrone to human duodenal and submandibular glands. Issue 5 (May 1978) - Heitz, P U; Kasper, M; van Noorden, S; Polak, J M; Gregory, H; Pearse, A G
Abstract : Urogastrone has been localised by immunostaining to granules of the cells of human duodenal (Brunner's) glands and their ducts and of acinar cells in the human submandibular gland. The immunoreactive peptide is present in large quantities in duodenal glands and their secretory ducts. Urogastrone or human epidermal growth factor promotes cellular proliferation in vivo as well as in vitro and inhibits gastric acid secretion and may, therefore, be one of the duodenal factors inhibiting gastric activity. Thus it may have an important regulatory and protective function for the intestinal mucosa and may possibly become a useful therapeutic agent.